A revision of Trimuricea Gordon, 1926 (Cnidaria: Octocorallia: Plexauridae) with the description of six new species - Samimi-Namin, Kaveh; Ofwegen, Leen P. Van (Zootaxa, 2016)
The genus Trimuricea Gordon, 1926 is revised. An overview and identification key of all presently known Trimuricea species is given. The type material of Trimuricea africana Gordon, 1926, T. reticulata (Thomson & Simpson, 1909), T. merguiensis Gordon, 1926, T. inermis (Nutting, 1910), T. magna (Nutting, 1910) and T. caledonica Grasshoff, 1999, is re-examined. Trimuricea andamanensis (Thomson & Simpson, 1909) is assigned to Echinogorgia Kölliker, 1865, Trimuricea aff. reticulata (Samimi-Namin & van Ofwegen 2009a) is synonymised with T. persica n. sp.; and T. magna (Nutting, 1910) with T. inermis (Nutting, 1910). Furthermore, six new species are described and depicted, T. bicolor, T. flava, T. omanensis, T. persica, T. tuberculosa, and T. spinosa, increasing the number of known Trimuricea species to eleven.